Therapeutic Potential of Astragaloside IV Against Adriamycin-Induced Renal Damage in Rats via Ferroptosis - Qin, Lu-Yun; Guan, Peng; Wang, Jian-Xin; Chen, Yu; Zhao, Ya-Shuo; Yang, Sheng-Chang; Guo, Ya-Jing; Wang, Na; Ji, En-Sheng (Frontiers in Pharmacology, 2022)
Adriamycin (ADR) has been utilized to treat cancer for several decades. However, ADR-induced renal injury is one of the most common side effects accompanying ADR therapy. In the present study, we revealed that astragaloside IV (ASIV) was beneficial for renal injury caused by Adriamycin. We demonstrated that ASIV significantly ameliorated kidney injury, improved renal dysfunction, reduced oxidative stress, alleviated iron accumulation, and inhibited the induction of ferroptosis by ADR. ASIV also rescued the intracellular levels of nuclear factor-erythroid-2-related factor 2 (Nrf2) and promoted nuclear translocation of Nrf2. These protective effects of ASIV on renal injury might be attained through the ASIV-induced activation of the Pi3K/Akt signaling pathway. In vitro, the treatment of the HK-2 cells with fer-1 or deferoxamine mesylate obviously improved cell viability during Adriamycin administration. On the other hand, the protective role of ASIV can be abrogated by RSL3 to some extent. Moreover, ASIV lowered the expression of transferrin receptor 1 and divalent metal transporter 1 while enhancing the expression of ferropotin 1 and glutathione peroxidase 4 in ADR administrated cells, the effects of which were akin to those of deferoxamine mesylate. Furthermore, ASIV increased the phosphorylation of Pi3K, Akt, and the expression of Nrf2 and glutathione peroxidase 4 compared to HK-2 cells stimulated by ADR. However, Pi3K inhibitor LY294002 abrogated these activations. In conclusion, ferroptosis may involve in ADR-induced nephrotoxicity, and ASIV might protect nephrocytes against ADR-induced ferroptosis, perhaps via activations of the Pi3K/Akt and Nrf2 signaling pathways.